Effects of concomitant immunomodulators on the pharmacokinetics, efficacy and safety of adalimumab in patients with Crohn's disease or ulcerative colitis who had failed conventional therapy. Issue 1 (7th November 2016) - Colombel, J.‐F.; Jharap, B.; Sandborn, W. J.; Feagan, B.; Peyrin‐Biroulet, L.; Eichner, S. F.; Robinson, A. M.; Mostafa, N. M.; Zhou, Q.; Thakkar, R. B.
Summary: Background: Adalimumab is approved for use in patients with moderate to severe Crohn's disease (CD) or ulcerative colitis (UC) who have not achieved disease control with conventional therapies including corticosteroids and/or immunomodulators (IMM). Aim: To analyse six studies that examined efficacy, pharmacokinetics and safety of combination IMM/adalimumab therapy, compared with adalimumab monotherapy in patients with inadequate disease control on conventional therapy. Methods: Patients with moderate to severe CD or UC from randomised, double‐blind, placebo‐controlled trials were analysed. Adalimumab was added to background therapy; patients were categorised as receiving adalimumab monotherapy (CD induction, n = 245, maintenance, n = 185; UC induction, n = 213, maintenance, n = 157) or combination therapy (CD induction, n = 139, maintenance, n = 139; UC induction, n = 140, maintenance, n = 100) according to baseline immunomodulator use. Efficacy was reported for the intent‐to‐treat populations from each study, with remission defined as CD activity index <150 for CD and Mayo score ≤2 with no subscore >1 for UC. Safety was assessed via adverse events. Results: The proportions of patients achieving remission were similar for adalimumab monotherapy and immunomodulator combination therapy in all studies. Median adalimumab concentrations at week 4 or 8 were numerically but not significantly higher with adalimumab combination therapy vs. monotherapy in the CD and UC studies respectively. Incidence and rate of adverse events was similar for adalimumab monotherapy and combination therapy. Conclusions: Post hoc analysis of six randomised, controlled trials demonstrated no efficacy benefits with immunomodulator/adalimumab combination therapy, compared with adalimumab monotherapy in CD and UC patients with inadequate disease control on conventional therapy; the safety of the two treatment approaches was comparable.